2005
DOI: 10.2165/00002512-200522100-00006
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Medications and Hip Fractures in the US

Abstract: This is the first national Veterans Health Administration hip fracture hospitalisation study that temporally linked outpatient fall-related medications in hip-fracture patients with matched controls. We found that of veterans with hip-fracture hospitalisations, 70% were prescribed outpatient medications from selected major drug categories that may potentially increase fall risk. Moreover, over one-third of hip-fracture patients received concomitant prescriptions of drugs from multiple selected drug categories.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…In contrast to our findings, a number of case-control studies using automated data have reported increased risk of hip fracture with antidepressant use. [41][42][43][44][45][46] This study design can be more vulnerable to bias owing to unmeasured covariates. 47 One cohort study has also reported a 65% increase risk of hip fracture with antidepressant therapy.…”
Section: Fracturementioning
confidence: 99%
“…In contrast to our findings, a number of case-control studies using automated data have reported increased risk of hip fracture with antidepressant use. [41][42][43][44][45][46] This study design can be more vulnerable to bias owing to unmeasured covariates. 47 One cohort study has also reported a 65% increase risk of hip fracture with antidepressant therapy.…”
Section: Fracturementioning
confidence: 99%
“…Antidepressants are one of the most commonly prescribed drugs in the Western world and have been reported to be associated with an increased risk of fractures [6][7][8][9][10][11][12][13][14][15][16]. Selective serotonin reuptake inhibitors (SSRIs) are recommended for first-line pharmacological management of depression because they are considered safer and better tolerated [17] than other types of antidepressants.…”
Section: Introductionmentioning
confidence: 99%
“…In trying to reverse the wide distribution of benzodiazepines among anxious older adults, several authors have warned against pharmacologic treatments of late-life anxiety in general because even the prescription of safer psychotropic drugs, such as selective serotonin reuptake inhibitors (SSRIs), may be problematic in older adults [42]. Recent studies indicate that SSRIs and tricyclic antidepressants may also induce a heightened risk of falls, fractures, and cognitive impairment [43]. On the other hand, a psychological intervention may not always be feasible or successful.…”
Section: Pharmacologic Interventionsmentioning
confidence: 99%